1983
DOI: 10.1037/0097-7403.9.2.105
|View full text |Cite
|
Sign up to set email alerts
|

Signaled tailshock is perceived as similar to a stronger unsignaled tailshock: Implications for a functional analysis of classical conditioning.

Abstract: Water-deprived rats given fixed-electrode, variable-intensity tailshock at random times rated each trial by pressing either a "high-aversiveness" or "low-aversiveness" lever in order to obtain water. Trials on which a warning signal preceded tailshock resulted in more "high-aversiveness" leverpressing than did otherwise equivalent unsignaled trials. The magnitude of this effect increased and decreased as a function of several parameters including signal-shock interval, signal duration, and range and absolute v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

1983
1983
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 41 publications
2
22
0
Order By: Relevance
“…It appears, therefore, that predictable shock may be more aversive (in terms of physiological stress responses) than unpredictable shock under certain experimental conditions. Pitman et al (1995) showed that greater predictability of shock was associated with higher plasma corticosterone and norepinephrine levels, taken to be indicative of chronic stress, supporting the conclusions of Miller et al (1983). Pitman et al (1995) believe that signals reliably predicting shocks cause sensitisation of central neural control of adrenocortical activity, whereas unpredictable shocks cause habituation of the central nervous system to occur.…”
Section: Study Lengthsupporting
confidence: 53%
See 2 more Smart Citations
“…It appears, therefore, that predictable shock may be more aversive (in terms of physiological stress responses) than unpredictable shock under certain experimental conditions. Pitman et al (1995) showed that greater predictability of shock was associated with higher plasma corticosterone and norepinephrine levels, taken to be indicative of chronic stress, supporting the conclusions of Miller et al (1983). Pitman et al (1995) believe that signals reliably predicting shocks cause sensitisation of central neural control of adrenocortical activity, whereas unpredictable shocks cause habituation of the central nervous system to occur.…”
Section: Study Lengthsupporting
confidence: 53%
“…This finding implies that preference does not necessarily indicate the stressfulness of the various conditions. Arthur (1986) claims that it is nonsensical to conclude that predictable shock is less stressful when there is evidence (Miller et al, 1983) that rats experience predictable shock as more intense. It appears, therefore, that predictable shock may be more aversive (in terms of physiological stress responses) than unpredictable shock under certain experimental conditions.…”
Section: Study Lengthmentioning
confidence: 99%
See 1 more Smart Citation
“…All extant studies in humans were conducted using repeated pairings of discrete, noxious thermal or electrical stimuli as the unconditioned stimulus (UCS), usually with neutral visual or auditory stimuli as the conditioned stimulus (CS). Although conditioning-based methods are increasingly used in preclinical pain research to quantify pain [12], it has been virtually impossible to demonstrate conditioned hypersensitivity in rodents [13,14], even though electric shocks are used routinely as the UCS in fear-conditioning paradigms and conditioned stress-induced analgesia is a well-studied phenomenon [15].…”
Section: Introductionmentioning
confidence: 99%
“…Because observing behavior has been seen in situations that appear to be devoid of both overt and covert preparatory responding (e.g. Miller et al 1983), preparatory responding is not a likely alternative explanation of observing behavior that could obviate the need for other explanations such as secondary reinforcement. However, the absence of preparatory responding in these cases stems largely from the use of specific preparations that make preparatory responding unlikely, such as fixed electrodes for shock delivery.…”
Section: Department Of Psychology State University Of New York Atmentioning
confidence: 99%